Feminist literary critique and collective construction of knowledge through the book Moio, from Kattalin Miner - Galarraga Arrizabalaga, Haizea; Lasarte Leonet, Gema (EGAN, 2023)
This research paper analyzes a literary gathering carried out in one of the modules organized within the Basque Summer University (UEU) Summer Cour- ses of 2022, which revolves around the teaching and learning of literature and collective reading. More specifically, a collective and feminist critique was built around the book Moio. Gordetzea ezinezkoa zen (2019) from Kattalin Miner. Within the said gathering, 16 professors and two moderators intervened. Once the book was read by all participants, it was discussed, and the produced recording was then transcribed. For this, qualitative research was used, analyzing the data by means of a categorization system created ad-hoc with this study in mind. Thus, the central ideas were classified and categorized, and the results were obtained. One of the most relevant conclusions suggests that Moio is interesting to work on in the latest years of secondary school and during high school, both because of the literary style and the relevance of the topics it deals with, be it the transgen- der reality, transphobia, suicide, mourning, mental health, etc. All these topics have been considered appropriate due to the impact they have in the identity construction of that age group, as long as they are designed in advance, conside- ring student individual characteristics and making use of proper teaching me- diation.